2018
DOI: 10.3390/en11113165
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hydrothermal Liquefaction of Biomass: A Critical Review

Abstract: Hydrothermal liquefaction (HTL) of biomass is emerging as an effective technology to efficiently valorize different types of (wet) biomass feedstocks, ranging from lignocellulosics to algae and organic wastes. Significant research into HTL has been conducted in batch systems, which has provided a fundamental understanding of the different process conditions and the behavior of different biomass. The next step towards continuous plants, which are prerequisites for an industrial implementation of the process, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
161
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 238 publications
(162 citation statements)
references
References 95 publications
1
161
0
Order By: Relevance
“…In order to collect the largest amount of biocrude from these small reactors, a solvent extraction procedure was developed; it is technically not possible to separate the biocrude and the aqueous phase gravimetrically. This would instead be the preferred solution in case of large scale continuous processes and the same approach should be considered also in lab-scale experiments, as reported also by Castello, Pedersen and Rosendahl [9] Figure 3 reports the effects of the collection procedure on the composition of the light biocrude fraction (biocrude 1) and on the aqueous phase obtained from an experiment performed at 350 • C, 10 min, 10%. It is clearly visible that by using Procedure 1, the light biocrude has a higher amount of organics and, in particular, catechol, creosol, acetic acid, benzoic acid and 4-ethylguaiacol are under the detection limit in the case of Procedure 2.…”
Section: Comparison Of Extraction Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to collect the largest amount of biocrude from these small reactors, a solvent extraction procedure was developed; it is technically not possible to separate the biocrude and the aqueous phase gravimetrically. This would instead be the preferred solution in case of large scale continuous processes and the same approach should be considered also in lab-scale experiments, as reported also by Castello, Pedersen and Rosendahl [9] Figure 3 reports the effects of the collection procedure on the composition of the light biocrude fraction (biocrude 1) and on the aqueous phase obtained from an experiment performed at 350 • C, 10 min, 10%. It is clearly visible that by using Procedure 1, the light biocrude has a higher amount of organics and, in particular, catechol, creosol, acetic acid, benzoic acid and 4-ethylguaiacol are under the detection limit in the case of Procedure 2.…”
Section: Comparison Of Extraction Proceduresmentioning
confidence: 99%
“…The decrease in the O/C and the increase in the H/C ratio of BC1 with respect to the feedstock suggest that the production of light biocrude was mainly due to decarboxylation rather than dehydration, which, on the contrary, was more evident for the production of BC2 and the solid residues. Although Castello, Pedersen and Rosendahl [9] recently reported that favorable HTL conditions can be obtained also at supercritical condition, it is known that the HTL temperature range where the biocrude is maximized lies between 300 and 350 • C [8,34]. At lower temperatures, partial conversion occurs, whereas at higher values the production shifts towards gases and char.…”
Section: Elemental Analysis and Higher Heating Valuementioning
confidence: 99%
“…Significant research on HTL, and by association, nutrient recovery, has been performed in small-scale batch systems and mainly utilized algae as feedstock [7][8][9]. The next step toward the commercialization of biofuel production, which involves an HTL pilot-scale plant that operates in a continuous mode, has received considerably less attention [10]. Only a few published reports relate to nutrient recovery following bio-crude production via continuous HTL.…”
Section: Introductionmentioning
confidence: 99%
“…Through the last decade, hydrothermal liquefaction (HTL) has been gaining a prominent position in the production of sustainable liquid fuels [3]. HTL consists in reacting biomass in hot pressurized water, at pressures high enough to keep water in its liquid or even supercritical state.…”
mentioning
confidence: 99%